Examining the Relationship Between Lecturer Service Quality and Student Retention - Elizabeth Meiske Maythy Lasut (Journal of Educational Management Research, 2026)
This study aims to examine the relationship between lecturers’ service quality dimensions—assurance, tangibles, empathy, reliability, and responsiveness—and student retention in higher education. A quantitative correlational design was employed involving 212 first-year, second-semester students selected through convenience sampling. Data were collected using a self-constructed questionnaire based on a 5-point Likert scale and analyzed through descriptive statistics and Pearson Product-Moment correlation. The findings revealed that all dimensions of lecturers’ service quality were rated at a high level, with tangibles obtaining the highest mean score (4.05) and reliability the lowest (3.85). Student retention was also categorized as high (mean = 3.65). Furthermore, all service quality dimensions showed positive and significant relationships with student retention. Assurance (r = 0.453) and tangibles (r = 0.450) demonstrated the strongest relationships, followed by empathy (r = 0.337), reliability (r = 0.331), and responsiveness (r = 0.169). The study implies that higher education institutions should prioritize strengthening lecturers’ competence and professionalism while improving reliability in teaching practices to enhance student retention.